Dampak Pemecahan Saham Terhadap Likuiditas dan Abnormal Return di Bursa Efek Indonesia - Anggarini, Ni Putu Devi; Wiagustini, Ni Luh Putu (E-Jurnal Manajemen; Vol 4 No 3 (2015), 2015)
The purpose of this study was to determine the significance of differences in abnormal trading volume and abnormal returns before and after stock split.This study took 44 samples were split shares and listed on the Indonesia Stock Exchange in the period 2010-2013 using census method.Data analysis technique used was Wilcoxon Signed Ranks Test and Paired Sample T-Test with a window period during the 11 day event.The results showed that there were no significant differences in trading volume and abnormal returns before and after stock split.Results of this test indicate that the market didnot react to the events of stock split.
Keywords: stock split, liquidity, abnormal return